1994
DOI: 10.1007/bf00346037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation in organ transplant patients of a polymerase chain reaction test for CMV DNA applied on white blood cells and serum

Abstract: A polymerase chain reaction (PCR) test for CMV DNA was evaluated for clinical usefulness. Leukocytes and serum were sampled from 36 patients who had recently undergone organ transplantation. Clinical symptoms, virus culture, and IgG and IgM antibodies were used to identify, in retrospect, patients with CMV disease certified beyond all doubt, with probable disease, with asymptomatic infection, or without infection. PCR tests for CMV DNA in leukocytes (BC-PCR) and serum (SE-PCR) were then evaluated. BC-PCR was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Our prospective comparison of different PCR primers for the ability to amplify different regions of the CMV genome demonstrated that (i) the CMV DNA detected by primer pairs in PCR assays in our study was more frequently associated with PBL specimens than serum specimens; (ii) differences were also seen between PBLs and serum with regard to the time to the detection of CMV DNA by PCR prior to the onset of symptomatic CMV infection, in which CMV DNA from PBLs was a more sensitive target than CMV DNA from serum for the early detection of symptomatic CMV infection (17 versus 12 days); and (iii) in addition, positive PCR results were also more frequently associated with the primer pair directed to the HindIII-X fragment than with the EcoRI fragment D, the MIE gene, or the IEA1 gene primer pairs. Diagnostic PCR assays based upon the immediate-early region have frequently been used for the detection of CMV in clinical samples (4,6,8,11). However, this region of the CMV genome has been shown to possess sporadic sequence variation among clinical strains, and primer mismatching has been shown to reduce the amplification efficiencies of PCR assays (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our prospective comparison of different PCR primers for the ability to amplify different regions of the CMV genome demonstrated that (i) the CMV DNA detected by primer pairs in PCR assays in our study was more frequently associated with PBL specimens than serum specimens; (ii) differences were also seen between PBLs and serum with regard to the time to the detection of CMV DNA by PCR prior to the onset of symptomatic CMV infection, in which CMV DNA from PBLs was a more sensitive target than CMV DNA from serum for the early detection of symptomatic CMV infection (17 versus 12 days); and (iii) in addition, positive PCR results were also more frequently associated with the primer pair directed to the HindIII-X fragment than with the EcoRI fragment D, the MIE gene, or the IEA1 gene primer pairs. Diagnostic PCR assays based upon the immediate-early region have frequently been used for the detection of CMV in clinical samples (4,6,8,11). However, this region of the CMV genome has been shown to possess sporadic sequence variation among clinical strains, and primer mismatching has been shown to reduce the amplification efficiencies of PCR assays (2).…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the importance of using conditions that were described in the original publications for each primer set, we retested a subset of 34 specimens (PBL and serum specimens) from five patients by customized procedures (3,4,11,17). Our results (positive or negative) exactly matched those obtained in the original analysis by using standard PCR conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier studies on kidney transplant recipients, we have shown that viremia detected in the form of CMV DNA present in serum samples correlated well with clinical disease. 21 Recently, by the use of quantitative PCR, a significant correlation between maximum viral load in blood and CMV disease in this patient category and in liver transplant recipients was reported. 22,23 A consequence of these works and the present study is that quantitative CMV detection in other types of specimens such as serum or plasma or WBCs may be more instrumental for decisions regarding initiation of antiviral treatment as well as for evaluation of treatment effects.…”
Section: Discussionmentioning
confidence: 91%